Various presentations of the olfactory hallucination in two patients with migraine disease: Case report - Partovi, Omeed; Tolebeyan, Amir Soheil (Frontiers in Neurology, 2022)
Objectives To report two different presentations of migraine with the olfactory hallucinations. A case with the typical hallucinatory olfactory symptoms preceding migraine headaches and another case with longstanding olfactory hallucinations. Background Migraine prevails in about 12% of the general population, with the migraine aura accountable for at least one-third of these cases. The most common aura is the visual aura, followed by the sensory aura, speech, and motor auras. Olfactory hallucinations preceding the headache phase of migraine are rare. To date, the International Classification of Headache Disorders (ICHD) has not recognized them as a subset of migraine aura. Results This report presents a patient with a typical Phantosmia (PO) aura before her migraine headache and a patient who experiences a longstanding PO aura. Conclusion The olfactory hallucination may present differently in patients with migraine disease. Based on the clinical significance of migraine with olfactory hallucinations, we propose that the ICHD classify this phenomenon as a subtype of aura in the future. However, larger studies are still required to better assess the pathophysiology of this phenomenon.